Application and Analysis of Power IGBT Device in Three-level NPC Topology - ZHAO Zhenbo; WANG Heng (Kongzhi Yu Xinxi Jishu)
It discussed the basic working principles of three-level topology as well as its corresponding commutation loops, defined the maximum DC-link voltage in continuous operation with given FIT curves by considering reliability requirements, and brought up a solution of three-level topology with IGBT modules by analyzing its chip technologies and housing features. Taking 4.5kV IGBT as an example, it studied the different switching characteristics caused by kinds of stray inductances and junction temperature in three-level topology, and proposed some suggestions about current sharing and symmetric layout of inverter design.